Auditoría de control interno al área de logística y su relación con la toma de decisiones de la hacienda el bosque, cantón Quevedo, periodo 2012. - Cornejo Erazo, Betty Marina (2015)
This research was aimed to audit the Internal Control Area Logistics and its relationship with decision making Hacienda Forest, Quevedo Canton, period 2012. The Hacienda El Bosque is located in the Quevedo Canton, in 2½ kilometer route Valencia. It is a relatively small company dedicated to the production of palm oil, this assessment was specifically directed to the area of logistics, the general objective of the proposed research; determine the influence of an audit of internal control in the area of logistics and its relationship with decision making, the specific objectives were: measure the effectiveness and efficiency of operations performed in the area of logistics, assess the reliability of financial reporting and verifying compliance with laws, policies and regulations established for the department. The research methodology allowed for this evaluation was the analysis, the source of primary and secondary data, the techniques were implemented direct observation, interviews, questionnaires and flowcharts. In the process of evaluation found that a moderate level of high confidence is handled with a 69.47% and a risk level of 30.53% in the efficiency of the activities, it was found that does not take proper inventory management and archiving relevant documentation clearance processes, thus obtaining a confidence level of 33% and a risk level of 67%. We also verified that partially meets instituted policies for the area of logistics, with a score of 66% with a confidence level and a risk level of 34%. While laws and regulations applicable to the company comply with a confidence level of 71.43% and 28.57% risk